Actividad anticolinesterásica e hipoglucemiante de extractos obtenidos de hongos Basidiomicetos del cantón Loja y Saraguro - Armijos Celi, Karla Fernanda (2018)
Abstract:A great variety of wild mushrooms are distributed in ecosystems of southern Ecuador and the research of their nutritional value or pharmacological properties has been limited, focusing mainly on ecological factors. For this reason, the aim of the present stuy was to value the pharmacological potential of 20 specimens of basidiomycete fungi collected in Loja and Saraguro cantons. From the fruiting bodies of each genus, extracts were obtained using methanol and water, which were evaluated against the enzymatic systems: α-glucosidase, α-amylase and acetylcholinesterase. For α-glucosidase, the highest inhibitory capacity was obtained for Laetiporus sp. (EM-562) and Gerronema sp. (EM-783) with IC50 values of 47,55 and 56.42 μg/mL respectively. In α-amylase the most representative extracts were: Laetiporus cf. sulphureus, Ganoderma cf. amazonense, Stereum sp., Oudemansiella platensis, Macrolepiota procera, Gerronema sp., Laetiporus sp. (EM-785), Trametes versicolor, Schizophyllum comune, Stereum cf. hirsutum and Cf. Entoloma, which reached values between 0.042 and 0.73 μg / mL. None of the 20 samples showed a percentage of inhibition higher than 50% against acetylcholinesterase, at a maximum dose of 2 mg / mL.